Pendekatan Swara Dalam Mengukur Popularitas Platform Streaming Musik Melaui Social Network Analysis Berbasis Percakapan Twitter - Arjuanda, Resa; Wibisono, Setyawan (STIKOM Tunas Bangsa Pematangsiantar, 2024)
In the digital era, the popularity of music streaming platforms is important in everyday life. To understand the popularity of music streaming platforms, Twitter social network analysis was used with the SWARA approach. The SWARA method provides values for important criteria in decision making. This approach helps understand user perceptions of the platform and strengthen marketing strategies. The WASPAS method is used to solve decision making problems by combining the Weighted Sum Model and the Weighted Product Model. The main music streaming platforms analyzed are Spotify, YouTube Music, Joox, Apple Music, Langit Music, and Music Bagus. Data is collected from Twitter conversations to identify conversation trends and user sentiment. Social network analysis was carried out to map relationships between individuals in the Twitter community. Centrality metrics are used to identify key actors in the network. Thus, this research provides insight into the dynamics of the popularity of music streaming platforms and their influence on Twitter users and provides a basis for more effective marketing strategies in the music industry.